An open label pilot study of supraerythemogenic excimer laser in combination with clobetasol spray and calcitriol ointment for the treatment of generalized plaque psoriasis. (3rd May 2016) - Levin, Ethan; Nguyen, Catherine M.; Danesh, Melissa J.; Beroukhim, Kourosh; Leon, Argentina; Koo, John
Abstract: A common therapeutic modality for psoriasis includes the combination of phototherapy with topical treatments. The recent development of targeted phototherapy with the excimer laser and spray formulations for topical treatments has increased the efficacy and convenience of these combinational therapies. Herein, we aim to assess the efficacy of a novel combination of therapies using the 308 nm excimer laser, clobetasol propionate spray and calcitriol ointment for the treatment of moderate to severe generalized psoriasis. In this 12-week study, patients with moderate to severe psoriasis received twice weekly treatments with a 308-nm excimer laser combined with clobetasol proprionate twice daily for a month followed by calcitriol ointment twice daily for the next month. Of the 30 patients enrolled, 83% of patients (25/30) achieved PASI-75 [65–94%, 95% confidence interval (CI)] at week 12. For PGA, there was an estimated decrease of 3.6 points (3.1–4.1, 95% CI, p < 0.0005) by week 12. In conclusion, the combination of excimer laser with alternating clobetasol and calcitriol application has shown to be a promising combination of therapies for the treatment of moderate to severe generalized psoriasis. Further evaluation may be conducted with a larger study inclusive of control groups and head-to-head comparisons against topical steroid and UVB therapy as monotherapies.